Antibacterial Evaluation of Snake Weed (Euphorbia hirta L.) - K.G. Raja Rao, O. Aniel Kumar, L. Mutyala Naidu and (Journal of Phytology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Ethanol, Methanol, Chloroform and Aqueous (water) extracts of leaf, stem, root and whole plant of Euphorbia hirta L. (Euphorbiaceae) were used to evaluate antibacterial activity. The agar-well diffusion assay was employed against several Gram-positive (Bacillus subtilis and Staphylococcus aureus) and Gram-negative (Escherichia coli, Klebsiella pneumoniae and Proteus vulgaris) bacterial species. Aqueous and chloroform extracts of stem and root did not express any activity. Antibacterial activity was recorded in the order of ethanol, methanol, aqueous and chloroform extracts. Among these extracts ethanol and methanol extracts of leaf and whole plant were more effective and significant than aqueous and chloroform extracts in inhibiting the growth of the pathogenic bacteria under study, but were less potent when compared to that of tetracycline used as positive control. Phytochemical screening of the plant revealed the presence of tannins, flavonoids, alkaloids, glycosides and saponins. The study scientifically validates the use of plant in traditional system of medicine to treat various diseases.